Gospel duets with treasured friends [compact disc] - Lee, Brenda, 1944- (Provident, 2007)
Brenda Lee sings some of her favorite gospel tunes with the help of a few close friends. Guests heard on this recording include Dolly Parton, George Jones, Huey Lewis, Pam Tillis, Martina McBride and many more. Features a total of 12 tracks.